Influence of Morphological Characters on the Yield of Apricot (Prunus armeniaca L.) - A Statistical Approach - P K Mahajan (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2006)
Discriminate Analysis was carried out to formulate the categorization rule for allocating the apricot tree to "High Yielder Group" and "Low Yielder Group". Factor Analysis method was also applied to extract the basic factors underlying the observed morphological characters of apricot for both the High and Low Yielder groups. The study brought out five basic factors explaining 69.35% of the total variation in the case of High Yielder population and six factors explaining 74.14% of the total variation in the case of Low Yielder population, respectively. The first factor in both the populations contains the same variables viz. stem girth, number of branches and leaf area which indicate that these variables play an appreciable/significant role in increasing the yield of apricot (21 % in the case of High Yielder and 16.33% in the case of Low Yielder population.